2010
DOI: 10.1007/s00066-010-2069-6
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid a Radiosensitizer in Head and Neck Squamous Cell Carcinoma Cell Lines

Abstract: Betulinic acid could be a promising treatment agent in radioresistant head and neck cancer. A combination of betulinic acid with radiotherapy seems to be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 21 publications
4
20
0
Order By: Relevance
“…Bache et al used BetA at a concentration of 10 µM and demonstrated that radiosensitization ability of BetA could be enhanced in hypoxic condition (51); our study agreed with theirs, while whether Sp1/PTEN pathway involves in hypoxic-induced radiosensitization ability enhancement of BetA is still unknown. Furthermore, there are also several mechanisms reveled underlying BetA-induced radiosensitization (50,51,59). However, our funding could be another important mechanism underlying the BetA enhancement of radiosensitization besides the other previously reported mechanisms (50,51,59), and further supported the assumption that BetA could be a clinically available and promising enhancer of tumor radiotherapy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Bache et al used BetA at a concentration of 10 µM and demonstrated that radiosensitization ability of BetA could be enhanced in hypoxic condition (51); our study agreed with theirs, while whether Sp1/PTEN pathway involves in hypoxic-induced radiosensitization ability enhancement of BetA is still unknown. Furthermore, there are also several mechanisms reveled underlying BetA-induced radiosensitization (50,51,59). However, our funding could be another important mechanism underlying the BetA enhancement of radiosensitization besides the other previously reported mechanisms (50,51,59), and further supported the assumption that BetA could be a clinically available and promising enhancer of tumor radiotherapy.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, there are also several mechanisms reveled underlying BetA-induced radiosensitization (50,51,59). However, our funding could be another important mechanism underlying the BetA enhancement of radiosensitization besides the other previously reported mechanisms (50,51,59), and further supported the assumption that BetA could be a clinically available and promising enhancer of tumor radiotherapy. According to our results, the enhancement of radiosensitization by BetA could be compromised in tumors with aberrant PTEN.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Several studies have demonstrated that addition of chemotherapy (CT) to adjuvant RT may be beneficial for patients with advanced OSCC [1,2,14,47,49]. The rationale to incorporate CT into multimodal treatment schemes are the synergistic effects with RT to improve the tumor cell kill by inhibiting the DNA repair in tumor cells, the decrease in tumor mass, the subsequent reoxygenation radiosentizing hypoxic tumor cells, selective toxicity depending on the cell cycle phase and induction of apoptosis [5,6,21,46].…”
Section: Introductionmentioning
confidence: 99%
“…Several treatment approaches exist for locally advanced squamous cell carcinoma of the head and neck (SCCHN) [5,8,12,16]. Many patients are treated with surgery followed by radiotherapy or followed by concurrent radiochemotherapy.…”
mentioning
confidence: 99%